Fifty shades freed - James, E. L. (New York Vintage Books, 2011)
Even though Christian and Anastasia are now a proper couple, they still have many obstacles to overcome, including Christian's past coming back to haunt Anastasia.
Originally published: Australia : The Writer's Coffee Shop Publishing House, 2011.
Keywords: Sexual dominance and submission -- Fiction; Erotic fiction; Love stories